2020
DOI: 10.3390/molecules25071631
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Gas Phase Acidity of Substituted Benzoic Acids Using Density Functional Concepts

Abstract: A theoretical study of the effect of the substituent Z on the gas phase acidity of substituted benzoic acids ZC6H4COOH in terms of density functional theory descriptors (chemical potential, softness and Fukui function) is presented. The calculated gas phase ΔacidG° values obtained were close to the experimental ones reported in the literature. The good relationship between the ΔacidG° values and the electronegativity of ZC6H4COOH and its fragments, suggested a better importance of the inductive than polarizabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…A study by Karty and co‐workers showed that the experimental deprotonation enthalpies of lactone enolates were in good agreement with the B3LYP/6‐31+G(d) calculations 20 . A recent study by Amador‐Balderas and co‐workers showed the B3LYP/6‐311++G(2d,2p) level of calculated gas‐phase acidities had a good correlation with the experimental data of substituted benzoic acids 22 . The M06‐2X DFT method showed good robustness in thermochemistry, and M06‐2X with DFT‐D3 correction was statistically the best out of all hybrids in the benchmark study by Goerigk and Grimme 23,24 .…”
Section: Calculationsmentioning
confidence: 71%
“…A study by Karty and co‐workers showed that the experimental deprotonation enthalpies of lactone enolates were in good agreement with the B3LYP/6‐31+G(d) calculations 20 . A recent study by Amador‐Balderas and co‐workers showed the B3LYP/6‐311++G(2d,2p) level of calculated gas‐phase acidities had a good correlation with the experimental data of substituted benzoic acids 22 . The M06‐2X DFT method showed good robustness in thermochemistry, and M06‐2X with DFT‐D3 correction was statistically the best out of all hybrids in the benchmark study by Goerigk and Grimme 23,24 .…”
Section: Calculationsmentioning
confidence: 71%
“…In the literature, the features of GD of benzoic acid (BA) as the simplest representative of substituted aromatic acids are discussed in sufficient detail [ 26 , 43 , 44 , 45 , 46 ]. The influence of the nature of substituents on the energy of GD of meta - and para -substituted BA have been considered in [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…To give a flavor of the exciting research that is being published in Molecules , we here highlight some recent papers in the fields of molecular properties, chemical reactivity, and biologically relevant interactions. Amador-Balderas et al [ 2 ] used the conceptual and computational framework of density functional theory (DFT) to analyze how substituents affect the acidity of benzoic acids and found that the substituent effect of electron-releasing substituents (which decrease the acidity) increases as ortho > meta > para , and vice versa for electron-withdrawing substituent (which increase the acidity).…”
mentioning
confidence: 99%